KESALAHAN BERBAHASA PADA POSCAST PEMBELAJARAN BAHASA INDONESIA DI APLIKASI SPOTIFY SISWA SEKOLAH MENENGAH ATAS (SMA) - Satya Arifandanu; Daru Susanti (Adisam Publisher, 2023)
This study aims to describe the phonological level language errors on the Indonesian language learning podcast on the Spotify application and analyze the phonological level language errors found in the Indonesian language learning podcast on the Spotify application. The research method used in this research is descriptive qualitative method, descriptive qualitative research is a method used to analyze, describe various conditions and situations from various kinds of data to be solved. This data collection technique is in the form of listening and note-taking techniques, listen is a method carried out by listening to the use of language to get data, while the note-taking technique is a method of recording from the data obtained. The results of this study found as many as 72 pronunciation errors of language sounds from 13 podcast audio data about Indonesian language learning materials. The errors consisted of 26 phoneme changes, 32 phoneme omissions, and 17 phoneme additions. The results of the study found the sound of vowel phonemes /a/, /i/, /u/, /e/, /o/, vowel diphthongs /ai/, /au/, /oi/, /ei/, consonant phonemes /b/, /c/, /d/, /f/, /g/, /h/, /j/, /k /, /l/,/m/, /n/, /p/, /q/, /r/, /s/, /t/, /v/, /w/, /x/, /y/, /z/. and the place of articulation of consonants such as bilabials, nasal consonants and others. Therefore, the results of this study are known that Indonesian language teachers should use good and correct language, because after all the Indonesian language teacher is a role model for students in every speech that is spoken, especially when students listen to the explanation of Indonesian language subject matter.